Perubahan Fungsi Hunian Menjadi Komersial Terhadap Tarikan Perjalanan Di Perumnas Bumi Tlogosari, Kota Semarang - Velly Destasaminda; Yudi Basuki (Teknik PWK (Perencanaan Wilayah Kota), 2021)
The urban problem that is often experienced by developing countries is the high change of land use in a housing into commercial land. It happens because people often use existing facilities in urban areas regardless of their carrying capacity. The impacts that can be caused generally affect the capacity of transportation facilities and infrastructure. Therefore, changes in land use can affect trip generation. One of the transportation analyzes related to trip generation is trip attraction. The sample location chosen is in the Tlogosari Bumi Housing which has the characteristics of land use change from residential to multifunction land use. There are two types of data used, namely primary data and secondary data. The method used is descriptive analysis, and multiple linear regression analysis. The results of this study indicate that the attraction of travel on Tlogosari Raya street is influenced by the number of employees. The recommendation that needs to be done is to enforce permits to control land use change.